In-Silico Molecular Docking and Pharmaco-Kinetic Activity Analysis of Potential Inhibitors against SARS-CoV-2 Spike Glycoproteins - Mita Shikder; Kazi Ahsan Ahmed; Tasnin Al Hasib; Pranta Ray; Abul Bashar Ripon Khalipha; Md. Lutful Kabir (Applied Microbiology: Theory ＆ Technology, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) is a causative agent of the potentially fatal coronavirus disease (COVID-19). Coronavirus targets the human respiratory system primarily. It can also infect the gastrointestinal, hepatic, and central nervous systems of humans, avians, bats, livestock, mice, and many other wild animals, as these are primary targets of the pathogen. This study aims to screen out the most potent inhibitor for SARS-CoV-2 (COVID-19) spike glycoproteins among the selected drugs, and computational tools have been utilized for this purpose. The selected drugs have been designed to explore their structural properties in this study by molecular orbital calculation. To inhibit the spike glycoproteins, the performance of these drugs was also examined by molecular docking calculation. In improving the performance of drugs, non-bond interactions play a significant role. To determine the chemical reactivity of all the medicines, HOMO and LUMO energy values were also calculated. The combined calculations exhibited that Ledipasvir among the selected drugs can be the most potent drug to treat SARS-CoV-2 compared to other medications.